Copper (nickel) based composite coatings reinforced with nanosized oxides - Sakhnenko, N.; Ovcharenko, O.; Ved, M. (Functional Materials, 2015)
The work reports the method for copper and nickel based coatings reinforced by ultrafine particles of alumina or zirconia deposition. The electrolytes″ compositions as well as electrosynthesis modes are grounded. Considerable enhance in the both physical-mechanical properties and corrosion resistance of synthesized composite systems over traditional monolayer coatings by copper and nickel is shown.